Walking on the Wild Side: Indigeneity, Passion, and Nation in Guillermo Saccomanno’s La lengua del malón - Tokarz, Wojciech (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
Although the historical novel produced in Argentina after the fall of the last dictatorship has been characterized by the principle of inclusion, the representation of Indigenous peoples in the re-imagining of national narratives has contributed, ironically, to their marginalization. This article focuses on the ways La lengua del malón (2003) by Guillermo Saccomanno engages critically with national narratives from a peripheral position in order to escape the genre’s colonial limitations and proposes narrative strategies that allow the author not only to recognize the country’s Indigenous heritage, but also to acknowledge the continuous presence of Indigeneity in contemporary Argentinean culture.